2014
DOI: 10.1016/j.physd.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive network dynamics and evolution of leadership in collective migration

Abstract: The evolution of leadership in migratory populations depends not only on costs and benefits of leadership investments but also on the opportunities for individuals to rely on cues from others through social interactions. We derive an analytically tractable adaptive dynamic network model of collective migration with fast timescale migration dynamics and slow timescale adaptive dynamics of individual leadership investment and social interaction. For large populations, our analysis of bifurcations with respect to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 42 publications
(138 reference statements)
1
32
0
Order By: Relevance
“…We saw this when we looked at greedy optimization processes for fitness based on access to abundant resources or based on both predation and access to scarce resources. Pais and Leonard (2014) also found that heterogeneity in the weight given to social information can persist, both when the trait is determined by adaptive dynamics and when individuals selfishly change their strategies to improve their own fitness. That different models of different types of strategies give rise to heterogeneity suggests that it might be a common feature of strategies for gathering social information and that we might expect to see it in natural populations.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We saw this when we looked at greedy optimization processes for fitness based on access to abundant resources or based on both predation and access to scarce resources. Pais and Leonard (2014) also found that heterogeneity in the weight given to social information can persist, both when the trait is determined by adaptive dynamics and when individuals selfishly change their strategies to improve their own fitness. That different models of different types of strategies give rise to heterogeneity suggests that it might be a common feature of strategies for gathering social information and that we might expect to see it in natural populations.…”
Section: Discussionmentioning
confidence: 94%
“…The flock will eventually reach consensus with every v i = 1, as long as there is a path in the network from every node to at least one node that perceives the cue (Pais and Leonard 2014). In the Appendix A.2, we show that, if bird i does not perceive the cue, then…”
Section: How Information About a Cue Spreadsmentioning
confidence: 84%
See 2 more Smart Citations
“…Collective decision making in ideal human groups using the DDM and the interrogation paradigm is studied in [13]. Related collective decision making models in animal groups are studied in [14]. In this paper, we study collective decision making in ideal groups using the DDM and the free response paradigm.…”
Section: Introductionmentioning
confidence: 99%